Consumer Rights in the Fintech Lending Era Amid Legal Challenges of a Borderless World - Oktaviana Ayu Sekar A; Prastyanti, Rina Arum (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
The rapid expansion of fintech lending services, particularly cross-border peer-to-peer (P2P) lending, has created significant legal challenges concerning consumer protection. This study examines whether existing legal frameworks adequately safeguard consumer rights within the borderless digital lending environment. Utilizing a normative-juridical method combined with a comparative approach, the research analyzes Indonesia’s regulatory structure alongside selected international frameworks. The findings reveal substantial gaps in consumer protection, exacerbated by the proliferation of illegal online lending platforms, regulatory fragmentation across jurisdictions, and the misuse of personal data. National regulations often prove insufficient to address complex cross-border legal issues. This study underscores the urgency of global regulatory harmonization, enhanced national oversight mechanisms, and improved digital literacy among consumers. It concludes with recommendations for regulatory reform, the establishment of international supervisory cooperation, and the strengthening of institutional roles, particularly by financial and communication authorities, to ensure robust consumer protection in the evolving fintech lending ecosystem.